Locally-rooted directors - Axel Kind; Christophe Volonté (Review of Quantitative Finance and Accounting, 2024)
We study the influence of locally-rooted directors (LRDs)—board members with personal ties to a company's geographic location—on firm performance. On the one hand, LRDs may provide valuable local know-how and access to local networks. On the other hand, as their appointments may go back to social ties with insiders (e.g., corporate directors, top executives, or large shareholders), LRDs may be used to extract rents and lack relevant experience, business skills, and independence. Using the directors' alma mater as a proxy for local roots, LRDs turn out to be heavily overrepresented, making up 30% of all directors in our sample. We show that LRDs are negatively related to Tobin's Q. However, this finding does not apply to domestically-oriented companies, i.e., firms without material foreign sales, and firms in regulated industries. Thus, while the results indicate that LRDs harm firm performance on average, their presence may be optimal in some cases.
Keywords: G30; G34; 330; Corporate governance; Board of directors; Social ties; Firm value